A tenda de Deus entre os homens: estudo exegético de Apocalipse 21.1-5 - Nascimento, Ákilla Vicente Braga (2024)
The last two chapters of the Book of Revelation by John (Rev 21-22) describe the new creation as a result of the judgment and redemption process unfolding throughout the book. Among the symbols presented, the "tent of God" (21.3) stands out as a sign of God's dwelling among humanity. This work aims to perform the exegesis of Rev 21.1-5, focusing on the analysis of the symbol of the "tent of God" and its relationship with the theme of divine habitation within creation as developed in the Old and New Testaments. The first section of the research provides an evaluation of the textual aspects necessary for exegesis. Next, the analysis of the predominant literary genre in the Book of Revelation by John and an analysis of the book's structure are presented. Finally, a literary and theological assessment of the symbolism of Rev 21.1-5 is conducted. The research highlights the "tent of God" as an eschatological sign towards which the main symbols of God's presence in creation converge (Garden of Eden, Desert Tabernacle, Jerusalem Temple, Jesus Christ). This symbol synthesizes Christian hope, representing the moment when the glory of God bursts forth and fills all spaces of creation, turning the cosmos into a grand sanctuary inhabited by the Creator and shared by His creatures